Любовь и смерть всегда вдвоем: роман / Наталья Андреева - Андреева Наталья Вячеславовна (Любовь. ru, 2007)
Экземпляры: ФО-3 (201410) / Инвентарный номер: 50401 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6